The genus Pirenella Gray, 1847 (= Cerithideopsilla Thiele, 1929) (Gastropoda: Potamididae) in the Indo-West Pacific region and Mediterranean Sea - Reid, David G.; Ozawa, Tomowo (Zootaxa, 2016)
Members of the genus Pirenella are abundant inhabitants of intertidal sedimentary shores, often found in association with mangroves, on the continental margins of the western Pacific and Indian Oceans, and eastern Mediterranean Sea. Until recently, four morphological species were recognised in the tropical Indo-West Pacific region and classified in the genus Cerithideopsilla, while another species occupying the Mediterranean and Indian Ocean was classified as Pirenella conica. Molecular phylogenetic analysis has demonstrated that all these species are congeneric and here it is shown that the valid name for the genus is Pirenella. A recently published molecular study recognised a total of 16 species and the present work is a systematic account of these species. Of the 16, nine are described as new. Other significant nomenclatural acts are: fixation of type species of Pirenella as Pirenella mammillata J.E. Gray, 1847; designation of neotypes for Cerithium alatum Philippi, 1849, Cerithium microptera Kiener, 1841, Cerithium conicum Blainville, 1829, Pirenella mammillata J.E. Gray, 1847 and Murex cingulatus Gmelin, 1791; designation of lectotype for Cerithium retiferum G.B. Sowerby II, 1855. The species accounts include full synonymies, detailed descriptions of shells (based on 831 museum samples), distribution records and maps, reviews of life history, of habitat and of ecology, and some images of radulae. Details of shell sculpture are adequate for the diagnosis of most species. Distorted shells are common in some populations and are suggested to represent parasitised individuals. Some species are pests of fishponds in Southeast Asia and P. conica is the intermediate host of a trematode responsible for the human disease heterophyiasis, while others are threatened by habitat destruction.